Factors affecting access to dialysis for patients with end‐stage kidney disease in Sub‐Saharan Africa: A scoping review - Milipaak Japiong; Christine Kurtz Landy; Mary T. Fox; Joseph Mensah; Peter Adatara (Wiley, 2023)
Abstract Aims This scoping review examined the factors affecting access to dialysis for patients with end‐stage kidney disease in Sub‐Saharan Africa. Design Scoping review. Methods The scoping review is conducted following the Joanna Briggs Institute methodology for scoping reviews and modelled by Preferred Reporting Items for Systematic Reviews and Meta‐analyses extension for scoping review. Results A descriptive content analysis of 30 included articles revealed three main findings affecting access and use of dialysis: Health system-related factors, health provider-related factors and patient factors. Patient or Public Contribution Equity in renal replacement therapy access and use will require concerted advocacy for good public policy, healthcare delivery, workforce capacity and education.